From Essen Seele auf to Almanya – German-Turkish movies in intercultural foreign language teaching - Chmielewska, Kamila (Glottodidactica, 2014)
The ethnic and cultural variety of the German speaking societies influences all aspects of social existence. More and more citizens with Turkish background take part in the political and cultural life of their German-speaking home countries. This article aims to present the main tendencieswithin the German-Turkish cinema and to show the potential of these films, which can be used for fostering intercultural competence in German as a Foreign Language classes.